The Marseille Center for Mediterranean Integration : An Interview with World Bank Maghreb Director Mats Karlsson - World Bank (Washington, DC, 2012)
In today's world, when open discussions on an issue of national development interest, almost always come across a dimension that relates to managing integration. Development in one country, so to speak, is not easy. Put positively, joining forces together to deal with issues of inter-dependence will create a far stronger base for progress and global competitiveness. The author absolutely need to create new instruments to back up national efforts by also supporting nations' ways of handling common issues and dealing with transboundary challenges ranging from environmental pollution, migration, conservation of marine resources, communication networks, and urban growth to name a few. The Marseille Center for Mediterranean Integration tries to do exactly that, by providing a platform for communities of practice focused on development issues across the region to ask hard questions about themselves, find answers that will be actionable and in so doing, contribute to the prosperity of the region as a whole. By identifying critical knowledge gaps and developing policy guidelines, the Center will support leaders and other key stakeholders in the region to adopt evidence-based policy-making and jointly pursue common development goals.